CRM : A study of PNB at Karnal District (With special reference to Tele Banking) - Gupta, Shivani (Journal of Commerce and Trade, 2009)
Customer Relationship Management is a business strategy to acquire and retain the most valuable customer’s relationship. CRM requires a customer – centric business philosophy and culture to support effective marketing, sales and service processes. CRM applications can enable effective customer relationship management, if an enterprise has the right leadership, strategy, and culture. This study based on Customer relationship management in Punjab National Bank at Karnal Distt. for the duration of April 2008 to Dec. 2008. This paper has discovered that in a competitive environment, the one idea that is sure to succeed will be the customer centric model, where the organization builds long term strategic relationships with its customer. And PNB has been successful in achieving such relationship with customers.